Cerebrospinal Fluid Rhinorrhea due to Transethmoidal Encephalocele Following Occipital Meningioma Resection in an Adult: A Case Report - Radovnický, Tomáš; Bartoš, Robert; Vachata, Petr; Sameš, Martin (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2019)
Transethmoidal encephalocele is a rare condition in adult patients. It is usually diagnosed during childhood by cerebrospinal fluid (CSF) rhinorrhea, meningitis, a nasal mass, or seizures. We present a case of an adult woman with CSF rhinorrhea following resection of an occipital meningioma. The cribriform plate defect containing the encephalocele was diagnosed by computed tomography and magnetic resonance imaging. Transcranial surgery using a patch was performed successfully. We also discuss the possible pathophysiologic mechanisms of encephalocele and treatment options.
Keywords: rhinorrhea; encephalocele; transethmoidal